Modeling of an automated integral logistics system using colored petri nets (2019)
(Eng) A system is a set of heterogeneous elements that work in direct relation with each other for a specific pur - pose; through its automation, it is possible to carry out productive processes with machines, without the direct participation of a human operator. The Automated Integrated Logistics System (SALI by it’s acronym in Spanish) is a didactic environment that allows to emulate the activities and operation of a Logistic Dis - tribution Center (DC), developed at the New Granada Military University as a teaching and learning tool for engineering. The current system programming in the software system allows a serial processing of a purchase order, from the moment in which the customer, passing through all the stations, until it is sent to a delivered point, requires the product. The present investigation presents a modeling of the system through Colored Petri Nets (CPN) it’s made, with the purpose of achieve a better understanding of the dynamics of the system, the relationships between the stations, the flow of materials during the process and the cycles of these over the stations; as well as identifying the restrictive stations within the process that are susceptible to an improvement to be raised in a future work.